Agricultural Management Impacts on Soil Health: Methods for Large Spatial Scales. Issue 1 (1st November 2017) - Rottler, Caitlin M.; Brown, David P.; Steiner, Jean L.
Abstract : Core Ideas: Organic matter stratification in soil health–managed soil resembles native soil. Methods are appropriate for the large spatial scale and our chosen indicators. Methods involving immediate sample preprocessing require field modifications. Agriculture in the Southern Great Plains of the United States depends on precipitation and temperature thresholds for productivity. The region's climate and weather are variable, presenting farming challenges that are predicted to increase. Building and conserving healthy, resilient soil is one way farmers manage for future uncertainty. Few studies have compared soil health–managed and conventionally managed farms at the regional scale. To better understand management effects on soil health across the Southern Great Plains, we studied farms at 12 locations. We piloted the study using three of the locations, collecting soils from 10 fields per location and analyzing them for indicators of soil health. Our objective was to test the suitability of our experimental framework and identify additional indicators and analyses of interest. Our framework was generally suitable to the purpose of this study. We also noted that soil health–managed soils had organic matter stratification similar to native soils, which we plan to explore further.